Homogeneous catalyst containing Lewis acid as well as preparation method and application of homogeneous catalyst

By designing a homogeneous catalyst containing Lewis acid, using the imidazole and quaternary ammonium salt acid ionic liquid in metal center complex with metal cations, the stability and efficiency problems of existing catalysts in the cycloaddition reaction between CO2 and PO are solved, and the stability and efficiency of existing catalysts are achieved. It has high efficiency, low temperature catalytic effect and high thermal stability, and is suitable for industrial applications of carbonate chemicals.

CN119237012AActive Publication Date: 2025-01-03SHENYANG INSTITUTE OF CHEMICAL TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411139443.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-01-03
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

In the cycloaddition reaction of CO2 and propylene oxide (PO), existing catalysts have problems such as poor stability, low catalytic efficiency, harsh reaction conditions and high production costs, and it is difficult to take into account both high catalytic activity and reusable stability.

Method used

A homogeneous catalyst containing Lewis acid was designed, using a new structure acid ionic liquid with imidazoles, quaternary ammonium salts and quaternary phosphorus salts with metal centers. By complexing with metal cations, a low-temperature and high-efficiency catalytic cycloaddition reaction was obtained. and has high thermal stability and recycling stability.

Benefits of technology

It has achieved efficient catalytic cycloaddition reaction between CO2 and PO. The catalyst has high thermal stability and good recycling performance, strong catalytic activity and a low reaction temperature window, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237012A_ABST
    Figure CN119237012A_ABST
Patent Text Reader

Abstract

The invention discloses a homogeneous catalyst containing Lewis acid as well as a preparation method and application of the homogeneous catalyst, and belongs to the technical field of cycloaddition reaction catalysts. The Lewis acidic ionic liquid comprises positive ions and negative ions; the cations are ammonium salt cations or phosphorus salt cations containing imidazoles or straight chains; and the anions are halogen anions and comprise Cl or Br or I. The Lewis acidic ionic liquid disclosed by the invention is adjustable in acid strength, and has high thermal stability and capability of efficiently catalyzing cycloaddition reaction of ethylene oxide (EO) / propylene oxide (PO) and CO2. The catalyst is simple to prepare and good in cycling stability, and can simultaneously activate CO2 and epoxy compounds at a relatively low reaction temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a Lewis acid-containing homogeneous catalyst and a preparation method and application thereof, belonging to the technical field of cycloaddition reaction catalysts. Background Art

[0002] Carbon dioxide (CO2), as a typical greenhouse gas, is being emitted into the atmosphere uncontrollably, causing increasingly serious climate problems. From another perspective, CO2 can be used as a non-toxic, low-cost, renewable C1 resource. Therefore, converting CO2 into high-value-added, low-energy chemical raw materials is of great strategic significance. Propylene carbonate (PC) is widely used in organic synthesis, battery media, pharmaceutical intermediates, biodegradation, and metal extraction. In addition, PC is also used in transesterification and polycarbonate synthesis. The cycloaddition of CO2 and propylene oxide (PO) to synthesize PC has 100% atom economy, which makes it particularly attractive for industrial applications. To date, a large number of homogeneous and heterogeneous catalysts for the cycloaddition of CO2 and PO have been reported, such as metal halide salts, quaternary ammonium salts, quaternary phosphonium salts, ionic liquids (ILs), polyionic liquids, organic bases, metal complexes, metal-organic frameworks, conjugated organic frameworks, supported catalysts, etc. However, these catalyst systems still have problems such as poor stability, low catalytic efficiency, harsh reaction conditions, and high production costs to a certain extent. Therefore, the design and development of new and efficient catalysts is of great significance.

[0003] Ionic liquids (ILs) are a new type of green medium composed of organic cations and inorganic / organic anions with unique properties and diverse structures. Many reports have used ILs for the cycloaddition reaction of PO and CO2 and achieved valuable results. It has been reported that metal ions can act as Lewis acid sites to participate in the addition reaction of CO2 and PO, thereby accelerating the ring opening of PO. Xiao et al. synthesized a Acidic ionic liquid catalyst (1-(1-ethylcarboxyethyl)-3-methylimidazolium brominating agent) and zinc bromide (ZnBr2) as a co-catalyst catalyzed CO2 cycloaddition. Under the conditions of reaction pressure of 1.5MPa and reaction temperature of 110℃, the PO conversion rate can reach 70.8% after 1h of catalytic reaction; Cheng et al. used ZnBr2 and choline chloride (CHCl) two-component catalyst to catalyze CO2 cycloaddition. Under the conditions of reaction temperature of 110℃ and reaction pressure of 1.5MPa, the PO conversion rate can reach 99% after 60min of reaction. Therefore, traditional ionic liquid catalysts generally require Lewis acid as a co-catalyst to attack epoxides and accelerate the ring-opening process. Unfortunately, the most commonly reported co-catalyst ZnBr2 is easily deactivated due to the rough mixing of catalyst components and the loss of active centers.

[0004] In recent years, organic polymers and Zn 2+ The introduction of Lewis acid sites into catalysts through complex reactions has attracted widespread attention. Zhang et al. synthesized a new porous organic polymer (Py-Zn@IPOPI (I = Br, I, Ac)) and used it to catalyze CO2 cycloaddition at 120°C. The PO conversion rate reached 96% after 6 hours of reaction at a reaction pressure of 2.0 MPa; Xie et al. synthesized a zinc-coordinated conjugated microporous polymer (Zn-CMP) for catalytic CO2 cycloaddition. The PO conversion rate reached 94.1% after a reaction pressure of 3.0 MPa, a catalyst ratio of 0.2 mol%, a reaction temperature of 120°C, and a reaction time of 1 hour. These metal-containing compounds have good catalytic performance, and due to their complex catalytic site structure, they are easy to recycle and reuse multiple times. However, the synthesis process of these catalysts has the disadvantages of using highly polar solvents, complex purification process, and high cost. Therefore, it is of great significance to develop a simple and convenient Lewis acid complex catalyst for efficient cycloaddition reaction of EO / PO with CO2. Summary of the invention

[0005] In order to solve the problem that the catalysts in the prior art for synthesizing EC / PC by the cycloaddition reaction of EO / PO and CO2 are difficult to achieve both high catalytic activity and repeated use stability, the present application provides a Lewis acid-containing homogeneous catalyst and a preparation method and application thereof, which utilizes the design of new structural acidic ionic liquids of imidazoles, quaternary ammonium salts and quaternary phosphonium salts containing metal centers to obtain the ability to catalyze cycloaddition reactions at low temperature and with high efficiency, can simultaneously activate epoxy compounds and CO2 at low temperature, and has high thermal stability and cyclic stability.

[0006] This application adopts the following technical solutions:

[0007] A Lewis acid-containing homogeneous catalyst, wherein the Lewis acid-containing homogeneous catalyst is an acidic ionic liquid;

[0008] The acidic ionic liquid includes cations and anions;

[0009] The anion is a halogen ion;

[0010] The cation is selected from at least one of the cations of the structures shown in Formula I to Formula III;

[0011]

[0012]

[0013] Among them, R 1 , R 2 , R 3At least one independently selected from a C1-C6 alkane group, a C2-C6 olefin group, an aromatic group, and a C2-C6 cycloalkyl group;

[0014] Y is independently selected from at least one of Zn, Co, Cu, Fe, Mg, La, Al, Ni, Ce, Ca, Mn, Sb, Ag, Pb, Zr, and Sn.

[0015] Optional, R 1 , R 2 , R 3 Independently selected from at least one of -CH3, -CH2CH3, -(CH2)2CH3, and -(CH2)3CH3.

[0016] Optionally, the anion is selected from Cl - Br - ,I - At least one of them.

[0017] According to another aspect of the present application, a method for preparing the above-mentioned Lewis acid-containing homogeneous catalyst is provided, comprising the following steps:

[0018] S1, heating a reaction mixture containing a cation source, a halogenated acetic acid, and a solvent to react to obtain a precursor;

[0019] The cation source is selected from compounds containing at least one structure of imidazoles, linear ammonium salts, and linear phosphonium salts;

[0020] The precursor is an ionic liquid containing imidazole, straight-chain ammonium salt or straight-chain phosphonium salt cations and halogen-containing anions.

[0021] S2, subjecting the raw material mixture containing the precursor obtained in step S1 and the metal cation source to solid phase grinding reaction to obtain a Lewis acid imidazole ionic liquid.

[0022] Optionally, in step S1, the cation source is selected from at least one of the compounds represented by the structures of formula Ia, IIa, and IIIa;

[0023]

[0024] Among them, R 1 , R 2 , R 3 At least one independently selected from a C1-C6 alkane group, a C2-C6 alkene group, an aromatic group, and a C2-C6 cycloalkyl group.

[0025] Optionally, in step S1, the halogenated acetic acid is selected from at least one of chloroacetic acid, bromoacetic acid, and iodoacetic acid.

[0026] Optionally, in step S1, the solvent is selected from at least one of methanol, ethanol, acetonitrile, ethyl acetate, acetone, benzene, toluene, and xylene.

[0027] Optionally, in step S1, the usage ratio of halogenated acetic acid to cation source and solvent is 1 mol: 0.9-3 mol: 30-90 mL.

[0028] Optionally, in step S1, the usage ratio of the halogenated acetic acid to the cation source is selected from any value of 1 mol:0.9 mol, 1 mol:1 mol, 1 mol:1.5 mol, 1 mol:2 mol, 1 mol:2.5 mol, 1 mol:3 mol, or any range value therebetween.

[0029] Optionally, in step S1, the usage ratio of the halogenated acetic acid solvent is selected from any value among 1mol:30mL, 1mol:40mL, 1mol:50mL, 1mol:60mL, 1mol:70mL, 1mol:80mL, 1mol:90mL, or any range value therebetween.

[0030] Optionally, in step S1, the conditions for the heating reaction include: heating to 50-80° C. and reacting for 12-24 hours;

[0031] Optionally, in step S1, the conditions for the heating reaction include: heating to 50-60°C, 60-70°C, and 70-80°C in sequence, and reacting for 12-24 hours respectively.

[0032] Optionally, in step S1, 3 to 5 purification steps are further included after the heating reaction;

[0033] The purification step includes: adding a washing solvent 2 to 5 times the weight of the product to the product after the reaction, stirring, washing, and filtering;

[0034] The washing solvent is selected from at least one of cyclohexane, benzene, toluene, xylene, acetonitrile and ethyl acetate.

[0035] Optionally, in step S2, the metal cation source is selected from at least one of zinc acetate, cobalt acetate, copper acetate, ferrous acetate, magnesium acetate, lanthanum acetate, aluminum acetate, nickel acetate, cerium acetate, calcium acetate, manganese acetate, antimony acetate, silver acetate, lead acetate, zirconium acetate, and tin acetate.

[0036] Optionally, in step S2, the conditions for the solid phase grinding reaction include: the grinding time is 5 to 20 minutes.

[0037] Optionally, in step S2, the conditions for the solid phase grinding reaction include: the grinding time is selected from any value of 5 min, 7.5 min, 10 min, 12.5 min, 15 min, 17.5 min, 20 min, or any range between them.

[0038] Optionally, in step S2, the solid phase grinding reaction further includes 3 to 5 purification steps;

[0039] The purification step includes: adding a washing solvent 2 to 5 times the weight of the product to the product after the reaction, stirring, washing, and filtering;

[0040] The washing solvent is selected from at least one of methanol, ethanol, acetonitrile, ethyl acetate, acetone, benzene, toluene and xylene.

[0041] After purification, the high-purity Lewis acidic ionic liquid is obtained.

[0042] The cation is selected from at least one of the cations of the structures shown in formula III-1 to formula III-16;

[0043]

[0044]

[0045] According to another aspect of the present application, there is also provided an application of the above-mentioned Lewis acid-containing homogeneous catalyst or the Lewis acid-containing homogeneous catalyst prepared according to the above-mentioned preparation method in catalyzing the cycloaddition reaction of epoxide and CO2 to prepare propylene carbonate.

[0046] Optionally, the epoxide is selected from ethylene oxide and / or propylene oxide.

[0047] Optionally, the reaction temperature window of the homogeneous catalyst is 80-160°C.

[0048] Optionally, the reaction temperature window of the homogeneous catalyst is selected from any value of 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C or any range therebetween.

[0049] In the present application, C1-C6 refers to the number of carbon atoms contained. For example, "C1-C6 alkane group" refers to an alkane group containing 1 to 6 carbon atoms.

[0050] In the present application, "alkane group" is a group formed by losing any hydrogen atom from an alkane compound molecule. The alkane compound includes straight-chain alkanes, branched-chain alkanes, cycloalkanes, and cycloalkanes with branches.

[0051] In the present application, an "olefin group" is a group formed by losing any hydrogen atom from an olefin compound molecule.

[0052] In the present application, an "aromatic hydrocarbon group" is a group formed by an aromatic compound losing a hydrogen atom on the aromatic ring.

[0053] In the present application, "cycloalkyl" is a group formed by losing a hydrogen atom from a cycloalkane molecule.

[0054] In this application, "[ECOOHIM]Br" refers to 1-methyl-3-carboxyethylimidazolium bromide ([ECOOHIM]Br)

[0055] In the present application, "[EIMBr-COO]2Zn-10" refers to 1-methyl-3-zincethylimidazolium bromide.

[0056] In the present application, "PO" refers to propylene oxide and "EO" refers to ethylene oxide.

[0057] In this application, "CO2" means carbon dioxide.

[0058] In the present application, "PC" means propylene carbonate and "EC" means ethylene carbonate.

[0059] The beneficial effects of this application include:

[0060] The Lewis acid homogeneous catalyst provided in the present application is a Lewis acidic ionic liquid, wherein the active center is an electrophilic cation and a nucleophilic halogen ion, wherein the cation is a cyclic imidazole containing a metal atom or a linear amine or a phosphonium salt, and the anion is a halogen. The Lewis acidic ionic liquid has an adjustable acid amount, high thermal stability and the ability to efficiently catalyze cycloaddition reactions, is simple to prepare and has excellent catalytic activity, and has a lower catalyst reaction temperature window range in the catalytic cycloaddition reaction, especially in the catalytic EO / PO and CO2 cycloaddition reaction, using 4.76×10 -4 mol of [EIMBr-COO]2Zn-10 catalyst, the EC yield was 99.38%, and the TOF value was 247.88h -1 , and the PC yield was 99.18% and the TOF value was as high as 247.78h -1 The Lewis acidic ionic liquid of the present application as a Lewis acid-containing homogeneous catalyst has extremely strong EO / PO ring-opening and CO2 ring-addition capabilities, and therefore has important industrial application value in the field of carbonate chemical synthesis. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 Schematic diagram of the synthesis process of 1-methyl-3-carboxyethylimidazolium bromide ([ECOOHIM]Br) in Example 1 of the present application.

[0062] Figure 2 Schematic diagram of the synthesis process of [EIMBr-COO]2Zn-10 in Example 1 of the present application.

[0063] Figure 3 [EIMBr-COO]2Zn-10 prepared in Example 1 of the present application 1 H NMR spectrum.

[0064] Figure 4 [EIMBr-COO]2Zn-10 prepared in Example 1 of the present application 13 C NMR spectrum.

[0065] Figure 5 [EIMBr-COO]2Sn-10 prepared in Examples 2 to 16 of the present application 1 H NMR spectrum.

[0066] Figure 6 [EIMBr-COO]2Sn-10 prepared in Examples 2 to 16 of the present application 13 C NMR spectrum.

[0067] Figure 7 FT-IR spectra of [ECOOHIM]Br, [EIMBr-COO]2Zn (unwashed - containing acetic acid), fresh [EIMBr-COO]2Zn-10 and [EIMBr-COO]2Zn-10 after recycling during the preparation process of Example 1 of the present application.

[0068] Figure 8 FT-IR spectra of different Lewis acidic (metal atom) ionic liquids prepared in Examples 2 to 16 of the present application, including (a) [EIMBr-COO]2Co-10, (b) [EIMBr-COO]2Cu-10, (c) [EIMBr-COO]2Fe-10, (d) [EIMBr-COO]2Ce-10, (e) [EIMBr-COO]2Ni-10, (f) [EIMBr-COO]2Mn-10, and (g) [EIMBr-COO]2Zr-10.

[0069] Fig. 9 This is a comparison chart of the effects of different reaction temperatures on the cycloaddition reaction of PO and CO2 to synthesize PC when [EIMBr-COO]2Zn-10 prepared in Example 1 of the present application is used as a catalyst.

[0070] Fig.10This is a comparison chart of the effects of different CO2 initial pressures on the cycloaddition reaction of PO and CO2 when [EIMBr-COO]2Zn-10 prepared in Example 1 of the present application is used as a catalyst.

[0071] Fig.11 This is a graph for evaluating the cyclic stability of [EIMBr-COO]2Zn-10 as a catalyst prepared in Example 1 of the present application.

[0072] Fig.12 This is a comparison chart of the universality of the cycloaddition reaction of different epoxides with CO2 when [EIMBr-COO]2Zn-10 prepared in Example 1 of the present application is used as a catalyst.

[0073] Fig.13 [EIMBr-COO]2Zn-10, [EIMBr-COO]2Mg-10, [EIMBr-COO]3Al-10, [EIMBr-COO]2Ca-10, [EIMBr-COO]2Mn-10, [EIMBr-COO]2Cu-10, [EIMBr-COO]2Co-10, [EIMBr-COO]2Fe ... A comparison of the effects of [EIMBr-COO]2Ni-10, [EIMBr-COO]4Zr-10, [EIMBr-COO]3La-10, [EIMBr-COO]3Ce-10, [EIMBr-COO]3Sb-10, [EIMBr-COO]2Pb-10, [EIMBr-COO]Ag-10, and [EIMBr-COO]2Sn-10 as catalysts on the synthesis of PC by the cycloaddition reaction of PO and CO2.

[0074] Fig.14 A comparison chart showing the effects of [EIMBr-COO]2Fe-10, [EIMBr-COO]2Zn-10, [EIMBr-COO]3La-10, [EIMBr-COO]2Co-10, [EIMBr-COO]2Mg-10, and [EIMBr-COO]4Zr-10 prepared in Examples 1 to 16 of the present application as catalysts on the reaction of EO and CO2 cycloaddition to synthesize EC.

[0075] Fig.15 The effects of [EIMBr-COO]2Fe-10, [EIMBr-COO]2Zn-10, [EIMBr-COO]3La-10, [EIMBr-COO]2Co-10, [EIMBr-COO]2Mg-10, and [EIMBr-COO]4Zr-10 prepared in Examples 1 to 16 of the present application as catalysts on the cycloaddition reaction of EO and CO2 at low temperature (90°C).

[0076] Fig.16 [EIMBr-COO]2Zn-10, [EIMBr-COO]2Mg-10, [EIMBr-COO]3Al-10, [EIMBr-COO]2Ca-10, [EIMBr-COO]2Mn-10, [EIMBr-COO]2Cu-10, [EIMBr-COO]2Co-10, [EIMBr-COO]2 Fe-10, [EIMBr-COO]2Ni-10, [EIMBr-COO]4Zr-10, [EIMBr-COO]3La-10, [EIMBr-COO]3Ce-1 0. Physical pictures of [EIMBr-COO]3Sb-10, [EIMBr-COO]2Pb-10, [EIMBr-COO]Ag-10, [EIMBr-COO]2Sn-10. DETAILED DESCRIPTION

[0077] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0078] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0079] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0080] In the examples of the present application, acid amount calculation, nuclear magnetic H spectrum analysis, nuclear magnetic C spectrum analysis (AscendⅢ500MHz liquid-solid dual-purpose nuclear magnetic resonance instrument, Bruker, Switzerland) and infrared spectrum analysis (IRTracer-100 Fourier transform infrared spectrometer, Shimadzu, Japan), thermogravimetric and differential thermal analysis (TG-DTA8122), characterization analysis are all routine operations, and those skilled in the art can operate according to the instrument instructions.

[0081] The PO conversion, PC selectivity, PC yield and TOF value in the test example of this application are calculated as follows:

[0082] X PO / % = (n PC) × 100 / (n PC + n PO ) (1)

[0083] S PC / % = nPC × 100 / (n PC + n byproducts) (2)

[0084] Y PC / % = X PO × S PC (3)

[0085] TOF=(n PO × PC yield) / (n Cat. ×t)(4)

[0086] Where, X PO is the conversion rate of PO, S PC is the selectivity of PC, Y PC is the yield of PC, n PO is the molar mass of PO, n PC is the molar mass of PC, n Cat is the molar mass of the active sites in the catalyst, and t is the reaction time.

[0087] The EO conversion, EC selectivity, EC yield and TOF value in the test examples of this application are calculated as follows:

[0088] X EO / % = (nEC) × 100 / (n EC + n EO ) (1)

[0089] S EC / % = nEC × 100 / (n EC + n byproducts) (2)

[0090] Y EC / % = X EO × S EC (3)

[0091] TOF=(n EO ×EC yield) / (n Cat. ×t)(4)

[0092] Where, X EO is the conversion rate of EO, S EC is the selectivity of EC, Y EC is the yield of EC, n EO is the molar mass of EO, n EC is the molar mass of EC, n Cat is the molar mass of the active sites in the catalyst, and t is the reaction time.

[0093] Example 1 Lewis acid functionalized ionic liquid catalyst ([EIMBr-COO]2Zn)

[0094] (1) As attached Figure 1As shown in the steps, the precursor 1-methyl-3-carboxyethyl imidazole bromide ([ECOOHIM]Br) was synthesized: First, 1-methyl imidazole (0.05 mol) and bromoacetic acid (0.05 mol) were dissolved in 30 ml of acetonitrile in a 250 ml three-necked round-bottom flask. The mixed reagents were then refluxed at 70°C for 24 h, washed three times with ethyl acetate, and vacuum dried at 70°C for 24 h. The product [ECOOHIM]Br was a white solid with a yield of 96.67%.

[0095] (2) As attached Figure 2 As shown in the steps, a new type of Lewis acid (Zn 2+ ) Complex catalyst: First, [ECOOHIM]Br (0.04 mol) and zinc acetate (0.02 mol) were mixed into agate mortar. Solid phase grinding operations were performed for 5, 10, and 20 min, respectively. A white product was synthesized after the reaction, named EIMBr-COO]2Zn (unwashed-containing acetic acid). The synthesized product was washed 3 times with methanol to remove the acetic acid therein, and then vacuum dried at 70 °C for 24 h. The obtained white solid product was named [EIMBr-COO]2Zn-X, where X represents the grinding time. The products corresponding to the solid phase grinding operations of 5, 10, and 20 min were named [EIMBr-COO]2Zn-5, [EIMBr-COO]2Zn-10, and [EIMBr-COO]2Zn-20, respectively.

[0096] Examples 2 to 16 Different Lewis acid (metal ion) functionalized ionic liquid catalysts

[0097] The catalyst preparation process is the same as that in Example 1, except that the cation structure and raw materials are different, as shown in Table 1, and the grinding time is 10 min.

[0098] A series of Lewis acid functionalized ionic liquid catalysts containing different metal ions were synthesized in Examples 2 to 16 and were named [EIMBr-COO]aY-10 catalysts, wherein -10 represents the grinding time of 10 min, a represents different values ​​of metal ions (one of 1, 2, 3, and 4), and Y represents different metals (one of Zn, Co, Cu, Fe, Mg, La, Al, Ni, Ce, Ca, Mn, Sb, Ag, Pb, Zr, and Sn).

[0099] Table 1 Ionic liquids prepared in Examples 1 to 16

[0100]

[0101]

[0102] The actual photos of different Lewis acid functionalized ionic liquid catalysts prepared in Examples 1 to 16 are as follows: Fig.16 shown.

[0103] Test Example 1

[0104] The [EIMBr-COO]2Zn-10 prepared in Example 1 was subjected to 1 H NMR nuclear magnetic detection, the results are as attached Figure 3 As shown, 1 The HNMR spectrum shows hydrogen at different positions of [EIMBr-COO]2Zn-10. 1 H NMR (500 MHz, DMSO) δ9.05, 7.63, 4.75, 3.88, 3.40, 3.17, 2.50 proved the successful synthesis of the catalyst.

[0105] Test Example 2

[0106] The [EIMBr-COO]2Zn-10 prepared in Example 1 was subjected to 13 C NMR nuclear magnetic detection, the results are as attached Figure 4 As shown, 13 In the CNMR spectrum, carbons at different positions of [EIMBr-COO]2Zn-10 were observed. 13 C NMR (126MHz, DMSO) δ167.68, 136.98, 123.12, 122.16, 51.12, 39.16, 35.32.

[0107] Test Example 3

[0108] The [EIMBr-COO]2Sn-10 prepared in Example 1 was subjected to 1 H NMR nuclear magnetic detection, the results are as attached Figure 5 As shown, 1 The HNMR spectrum shows hydrogen at different positions of [EIMBr-COO]2Sn-10. 1 H NMR (500 MHz, DMSO) δ 9.12, 7.74, 7.72, 5.15, 3.91, 3.32, 2.50 proved the successful synthesis of the catalyst.

[0109] Test Example 4

[0110] The [EIMBr-COO]2Sn-10 prepared in Example 1 was subjected to 13 C NMR nuclear magnetic detection, the results are as attached Figure 6 As shown, 13 In the CNMR spectrum, carbon at different positions of [EIMBr-COO]2Sn-10 was observed. 13C NMR (126MHz, DMSO) δ168.14,137.62,123.73,123.24,49.71,39.60,35.98.

[0111] Test Example 5

[0112] The catalytic performance of the catalyst prepared in Example 1 was tested. First, appropriate PO and catalyst were added to the autoclave in sequence, and then the reaction system was sealed. Before the experiment, the autoclave was cleaned three times with CO2. After that, 2.6MPa of CO2 was injected into the reactor at room temperature, and then the reaction temperature was increased to the target value and stirred continuously until constant pressure. After the reaction was completed, the autoclave was cooled to room temperature, and then the remaining CO2 was slowly released. After each reaction, the mixture of PC and catalyst was separated under reduced pressure, and the collected [EIMBr-COO]2Zn-10 catalyst was directly used for the next run.

[0113] Test Example 6

[0114] The [ECOOHIM]Br, [EIMBr-COO]2Zn (unwashed) prepared in Example 1, fresh [EIMBr-COO]2Zn-10, and the method of Test Example 5 were used under the optimal reaction conditions (110°C, 2.6MPa, 4.76×10 -4 mol, 70min) for 6 cycles of cycloaddition reaction of PO and CO2, and the FT-IR spectrum of [EIMBr-COO]2Zn-10 was tested. The results are shown in the attached figure. Figure 7 As shown in Figure 1, the FT-IR characterization of the precursor [ECOOHIM]Br, [EIMBr-COO]2Zn-10 (unwashed), fresh [EIMBr-COO]2Zn-10, and recycled [EIMBr-COO]2Zn-10 was compared. The characteristic peaks of the imidazole ring group were clearly observed in all samples. 3149~2952cm -1 The absorption peak is caused by the CH stretching vibration of the alkyl group substituted by the imidazole ring. -1 and 1379cm -1 The absorption peak at 1168cm is caused by the stretching vibration of the C=N and C=C bonds in the imidazole ring. -1 There is an in-plane bending vibration peak at 839~793cm -1 The absorption peaks at 200 μm belong to the in-plane and out-of-plane bending vibrations of the CH bonds of the imidazole ring. 2+ During the functionalization process, the imidazole groups of all samples can be stably present. -1The absorption peak at 1732 to 1655 cm-1 is attributed to the C=O stretching vibration of the -COOH group in [ECOOHIM]Br. Compared with [ECOOHIM]Br, it can be clearly observed that the C=O absorption peak of [EIMBr-COO]2Zn-10 is from 1732 to 1655 cm-1. -1 This phenomenon indicates that the -COOH group becomes -COO after the complexation reaction. - . At 703 and 487cm -1 The absorption peak at is the stretching and rocking vibration characteristic of Zn-O bond, which is due to the Lewis acid (Zn 2+ ) replaces the H in the carboxylic acid of [ECOOHIM]Br + Surprisingly, after 6 cycles, the characteristic peak position and intensity of [EIMBr-COO]2Zn-10 remained unchanged, indicating that the homogeneous catalyst synthesized by the solid phase grinding method has excellent stability.

[0115] Test Example 7

[0116] FT-IR characterization and analysis of the ionic liquid [EIMBr-COO]aY-10 (a = 2, 3, 4M = Co, Cu, Fe, Ce, Ni, Mn, Zr) catalysts prepared in Examples 2 to 14 Figure 8 All prepared catalysts showed the same peaks associated with the imidazole ring. 3149~2952cm -1 The absorption peak is caused by the stretching vibration of the substituted alkyl CH on the imidazole ring. -1 The absorption peak is the stretching vibration of C=N in the imidazole ring, at 1379cm -1 The absorption peak is the stretching vibration of the C=C double bond in the imidazole ring. The CN bond of the imidazole ring is at 1168cm -1 There is an in-plane bending vibration peak at 582, 596, 482, 861, 587, 461 and 811 cm-1, and the absorption peaks at 839-793 cm-1 belong to the in-plane and out-of-plane bending vibration peaks of the CH bond of the imidazole ring. The results show that the imidazole groups of all samples can be stably present in the subsequent functionalization process of introducing Lewis acidic metal ions. -1The absorption peaks at are the stretching vibrations of Co-O, Cu-O, Fe-O, Ce-O, Ni-O, Mn-O, and Zr-O bonds. The above results show that Lewis acid functionalized ionic liquids [EIMBr-COO]2Co-10, [EIMBr-COO]2Cu-10, [EIMBr-COO]2Fe-10, [EIMBr-COO]2Ce-10, [EIMBr-COO]2Ni-10, [EIMBr-COO]2Mn-10, and [EIMBr-COO]2Zr-10 were successfully synthesized.

[0117] Test Case 8

[0118] As attached Fig. 9 As shown, [EIMBr-COO]2Zn-10 prepared in Example 1 was used as a catalyst as a typical example, and the method of Test Example 5 was used to test the effect of different reaction temperatures on the synthesis of PC by the cycloaddition reaction of PO and CO2. The reaction conditions were 0.14 mol PO, 2.6 MPa CO2, 4.76×10 -4 mol[EIMBr-COO]2Zn-10. The cycloaddition reaction catalyzed by [EIMBr-COO]2Zn-10 was carried out at 80, 90, 100, 110 and 120 °C, respectively. The catalytic reaction performance at different temperatures was evaluated according to the complete 100% conversion time of PO and presented in a histogram. Obviously, as the reaction temperature increased from 80 °C to 120 °C, the corresponding 100% conversion PO gradually decreased and showed the following order: 80 °C (450 min) > 90 °C (390 min) > 100 °C (300 min) > 120 °C (80 min) > 110 °C (70 min), while the related TOF values ​​showed the opposite order as shown below: 80 °C (38.51 h -1 )<90℃(44.54h -1 )<100℃(57.77h -1 )<120℃(216.92h -1 )<110℃(247.78h -1 ). Obviously, as the reaction temperature increases, the catalytic activity gradually increases. This may be because the increase in temperature promotes the movement frequency of CO2 molecules and enhances the collision between molecules, thereby promoting the rapid contact between CO2 and PO. However, extremely high temperatures will reduce the solubility of CO2 in PO, limit the mutual contact between the two, and are not conducive to the normal progress of the reaction. Therefore, 110℃ is the most suitable temperature for the cycloaddition reaction of PO and CO2.

[0119] Test Example 9

[0120] As attached Fig.10As shown, [EIMBr-COO]2Zn-10 prepared in Example 1 was used as a catalyst as a typical example, and the method of Test Example 5 was used to test the effect of different CO2 pressures on the synthesis of PC by the cycloaddition reaction of PO and CO2. The reaction conditions were 0.14 mol PO, 110 °C, 4.76×10 -4 mol[EIMBr-COO]2Zn-10. When the initial CO2 pressure is 1.8MPa (CO2 / PO molar ratio is 1 / 1), it takes 175min for PO to be completely converted into PC, and the TOF value is 99.02h-1. Under the condition of initial CO2 pressure of 2.2MPa (CO2 / PO molar ratio is 1.2 / 1), it takes 140min for PO to be completely converted into PC, and the TOF value is 124.00h-1. -1 When the initial CO2 pressure was 2.6MPa (CO / PO molar ratio was 1.6 / 1), the reaction time was shortened to 70min and the TOF value increased to 247.78h -1 It is obvious that when the initial CO2 pressure increases from 1.8MPa to 2.6MPa, the catalytic performance begins to increase. However, as the initial CO2 pressure continues to increase to 3.0MPa (CO / PO molar ratio is 2.0 / 1), the complete conversion time of PO is extended to 90min, and the TOF value decreases to 193.56h -1 . It can be seen that with the increase of the initial CO2 pressure, the complete conversion time of PO to PC first decreases and then slightly increases. The reaction time is shortest at a pressure of 2.6MPa. This is due to the effect of the initial CO2 pressure on the gas-liquid distribution of the reactants in the system. As the pressure increases, the concentration of CO in the PO phase increases, which is conducive to the cycloaddition reaction. However, excessive CO2 pressure will lead to a decrease in PO concentration and a dilution of the catalyst concentration. In this case, the interaction between PO and the active sites in the catalyst is weakened, thereby delaying the complete conversion of PO to PC.

[0121] Test Example 10

[0122] As attached Fig.11 As shown, [EIMBr-COO]2Zn-10 prepared in Example 1 was used as a catalyst as a typical example. Under the optimal reaction conditions (110°C, 2.6MPa, 4.76×10 -4 The cycloaddition reaction of PO with CO2 was carried out six times at 100 mol, 70 min) to evaluate its recyclability and reusability. After each run, the mixture of PC and catalyst was separated under reduced pressure, and the collected catalyst was directly used in the next run. Fig.11As shown in the figure, after 6 cycles, the selectivity and yield of PC remained basically unchanged (>99%), indicating that the [EIMBr-COO]2Zn-10 catalyst maintained excellent catalytic activity and stable active centers. In order to further confirm the superiority of the [EIMBr-COO]2Zn-10 catalyst, the structures of the new catalyst and the old catalyst were analyzed and compared by FT-IR. Figure 7 It can be seen that after 6 cycles, the characteristic peaks of [EIMBr-COO]2Zn-10 remain unchanged. Based on the above experimental results, [EIMBr-COO]2Zn-10 can be considered as a highly active, recyclable and promising catalyst for the cycloaddition reaction of PO and CO2.

[0123] Test Example 11

[0124] Taking [EIMBr-COO]2Zn-10 prepared in Example 1 as a typical catalyst, under the optimal reaction conditions (110°C, 2.6MPa, 4.76×10 -4 mol, 70min), epoxides with different substituents were used to carry out cycloaddition reaction with CO2 to synthesize the corresponding cyclic carbonates. Fig.12 As shown in the figure, after 70 min of reaction, the conversions of ethylene oxide, propylene oxide, 1,2-butylene oxide, epichlorohydrin and glycerol (a, b, c, d, e) reached 99.42%, 99.18%, 99.37%, 99.01% and 99.32%, respectively. Obviously, the conversion of epoxides remained basically unchanged with the increase of alkyl chain substitution of epoxides. At the same time, we noticed that the conversions of epichlorohydrin and ethylene glycol were higher. The halogen atom in epichlorohydrin is an electron-withdrawing group that can stabilize the intermediates formed during the ring-opening of epoxides, thereby promoting the cycloaddition reaction. The conversion of glycerol was satisfactory, which may be due to the formation of intermolecular hydrogen bonds between glycerol molecules. At the same time, in the cycloaddition reaction, ethylene glycol is both a substrate and a catalyst (hydrogen bond donor). With styrene oxide, phenyl glycidyl ester and allyl glycidyl ester (f, j and h) as substrates, the reaction time was extended to 150, 130 and 300 min, respectively, and the conversion rates were 99.20%, 99.27% ​​and 83.24%, respectively. This can be explained by the relatively strong steric site resistance (strong conjugation effect), which hinders the diffusion of molecules and the contact between active sites and epoxides. In addition, the strong steric hindrance in the substrate will weaken the electrophilic-nucleophilic ability of [EIMBr-COO]2Zn-10, which is not conducive to the ring opening of epoxides. In summary, [EIMBr-COO]2Zn-10 shows good catalytic versatility in the cycloaddition reaction of CO2 and epoxides.

[0125] Test Example 12

[0126] As attached Fig.13 As shown, [EIMBr-COO]2Mg-10, [EIMBr-COO]3Al-10, [EIMBr-COO]2Ca-10, [EIMBr-COO]2Mn-10, [EIMBr-COO]2Cu-10, [EIMBr-COO]2Zn-10, [EIMBr-COO]2Co-10, [EIMBr-COO]2Fe-10, [EIM Br-COO]2Ni-10, [EIMBr-COO]4Zr-10, [EIMBr-COO]3La-10, [EIMBr-COO]3Ce-10, [EIMBr-COO]3Sb-10, [EIMBr-COO]2Pb-10, [EIMBr-COO]Ag-10, [EIMBr-COO]2Sn-10 as catalysts, and their catalytic performance in the cycloaddition reaction of PO and CO2. The reaction conditions are 0.14 mol PO, reaction temperature 110 °C, 4.76×10 -4 When [EIMBr-COO]2Mg-10, [EIMBr-COO]3Al-10 and [EIMBr-COO]2Ca-10 were used as catalysts, the PC yields were only 85.69%, 10.21% and 4.14%, and the TOF values ​​were 214.08h -1 , 25.51h -1 and 10.34h -1 . In general, metal atoms with greater electronegativity can exhibit enhanced electron pair attraction and lead to an increase in the strength of the Lewis acid, while improving the catalytic cycloaddition efficiency. According to the order of metal activity and electron acceptance ability, it is theoretically expected that [EIMBr-COO]2Ca-10, [EIMBr-COO]2Mg-10, and [EIMBr-COO]3Al-10 will gradually increase. However, [EIMBr-COO]3Al-10 has a relatively poor catalytic efficiency in the cycloaddition reaction of PO and CO2. It may be that Al 3+ Ion and Br - The formation of strong coordination weakens the strength of Lewis acid. The poor catalytic efficiency of [EIMBr-COO]2Ca-10 in the cycloaddition reaction of PO and CO2 can be attributed to the poor catalytic efficiency of Ca 2+ The electronegativity of a molecule is relatively small, and its ability to acquire electrons is relatively weak.

[0127] When [EIMBr-COO]2Mn-10 and [EIMBr-COO]2Cu-10 were used as catalysts, the PC yields reached 48.52% and 13.17%, and the TOF values ​​were 121.22 h -1 and 32.90h -1. The three-dimensional orbitals of Mn and Cu are in half-filled and fully-filled states, respectively, which may be the reason for the poor catalytic efficiency. The metal central atom of the catalyst has a low electron affinity and a poor ability to obtain electrons, resulting in a decrease in the strength of the Lewis acid and a decrease in the catalytic cycloaddition efficiency. However, when [EIMBr-COO]2Zn-10, [EIMBr-COO]2Co-10, [EIMBr-COO]2Fe-10 and [EIMBr-COO]2Ni-10 were used as catalysts, the PC yields were 99.18%, 99.65%, 98.37% and 96.87%, respectively, and the TOF values ​​were 247.78h -1 , 248.96h -1 , 245.76h -1 and 242.01h -1 . This result can be attributed to the unequal atomic radii of the metal centers in [EIMBr-COO]2Zn-10, [EIMBr-COO]2Co-10, [EIMBr-COO]2Fe-10 and [EIMBr-COO]2Ni-10, resulting in unequal electron affinity and catalytic performance. When [EIMBr-COO]4Zr-10 was used as the catalyst, the PC yield was 96.65% and the TOF value was 241.46h-1, and the yield and TOF value were relatively poor. When [EIMBr-COO]3La-10 and [EIMBr-COO]3Ce-10 were used as catalysts, the PC yields reached 90.27% and 89.69%, and the TOF values ​​were 225.52h-1, respectively. -1 and 222.50h -1 . This result can be attributed to the fact that the atomic radius and electron affinity of the metal centers in [EIMBr-COO]3La-10 and [EIMBr-COO]3Ce-10 are basically equal, resulting in similar Lewis acid strength and catalytic performance in the cycloaddition of PO and CO2. The catalytic effect of poor metals (Sb or Pb) as active Lewis acid sites was also studied. When [EIMBr-COO]2Sn-10, [EIMBr-COO]3Sb-10 and [EIMBr-COO]2Pb-10 were used as catalysts, the PC yields (99.67%, 78.08%, 9.36%) and TOF values ​​(248.96h -1 、195.07h -1 and 18.26h -1 ) are not ideal. The reason why [EIMBr-COO]3Sb-10 has a better catalytic effect than [EIMBr-COO]2Pb-10 is that the atomic radius of Sb is much smaller than that of Pb, and the Lewis acid strength of the former is higher than that of [EIMBr-COO]2Pb-10. When [EIMBr-COO]Ag-10 is used as the catalyst, the PC yield is 3.01% and the TOF value is 7.52h-1 The yield and TOF value are poor. The reason for the poor catalytic efficiency of [EIMBr-COO]Ag-10 is that the 4d orbital of Ag is fully filled, the ability to obtain electrons is limited, and the Lewis acid strength is low.

[0128] Test Example 13

[0129] As attached Fig.14 As shown, the catalytic performance of [EIMBr-COO]2Fe-10, [EIMBr-COO]2Zn-10, [EIMBr-COO]3La-10, [EIMBr-COO]2Co-10, [EIMBr-COO]2Mg-10, and [EIMBr-COO]4Zr-10 prepared in Examples 1 to 16 in the cycloaddition reaction of EO and CO2. The reaction conditions are 0.14 mol EO, reaction temperature 110 °C, 4.76×10 -4 mol catalyst, reaction time 70min. When [EIMBr-COO]2Fe-10, [EIMBr-COO]2Zn-10, [EIMBr-COO]3La-10, [EIMBr-COO]2Co-10, [EIMBr-COO]2Mg-10, [EIMBr-COO]4Zr-10 were used as catalysts, the EO conversion rates were 99.67%, 99.38%, 99.54%, 99.65%, 99.24%, 99.27%, and the TOF values ​​were 248.96h -1 , 247.88h -1 , 248.12h -1 , 248.96h -1 , 248.71h -1 、247.01h -1 Obviously, compared with the cycloaddition reaction of PO and CO2, the conversion rate of ethylene oxide catalyzed by different catalysts remains basically unchanged, all greater than 99%. This shows that the synthesized catalyst has a higher catalytic efficiency for EO. This may be because the EO molecule has a symmetrical structure and is basically not affected by the spatial position. At the same time, the nucleophilic Br - After the EO ring is opened by ions, the intermediate formed can be stabilized. In summary, the above catalysts show good catalytic efficiency in the cycloaddition reaction of CO2 and EO.

[0130] Test Case 14

[0131] As attached Fig.15As shown, the catalytic performance of [EIMBr-COO]2Fe-10, [EIMBr-COO]2Zn-10, [EIMBr-COO]3La-10, [EIMBr-COO]2Co-10, [EIMBr-COO]2Mg-10, [EIMBr-COO]4Zr-10 prepared in Examples 1 to 16 in the cycloaddition reaction of EO and CO2. The reaction conditions are 0.14 mol EO, reaction temperature 90 ° C (low temperature), 4.76×10 -4 mol catalyst, reaction time 70min. When [EIMBr-COO]2Fe-10, [EIMBr-COO]2Zn-10, [EIMBr-COO]3La-10, [EIMBr-COO]2Co-10, [EIMBr-COO]2Mg-10, [EIMBr-COO]4Zr-10 were used as catalysts, the EC yields were 98.67%, 99.38%, 91.54%, 99.65%, 99.24%, 97.87%, and the TOF values ​​were 245.86h -1 , 247.88h -1 , 233.89h -1 , 248.96h -1 , 239.71h -1 、243.01h -1 The catalytic effect of [EIMBr-COO]3La-10 is relatively low, which can be attributed to the fact that the atomic radius and electron affinity of the metal center (La) are basically equal, resulting in the Lewis acid strength and catalytic performance of the cycloaddition of EO and CO2 being lower than other catalysts. From the experimental results, it can be concluded that even at lower temperatures, the EC yield is still satisfactory, indicating that the cycloaddition reaction of EO and CO2 is easier to proceed.

[0132] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A Lewis acid-containing homogeneous catalyst, characterized in that: The Lewis acid-containing homogeneous catalyst is an acidic ionic liquid; The acidic ionic liquid includes cations and anions; The anion is a halogen ion; The cation is selected from at least one of the cations of the structures shown in Formula I to Formula III; Among them, R 1 , R 2 , R 3 At least one independently selected from a C1-C6 alkane group, a C2-C6 olefin group, an aromatic group, and a C2-C6 cycloalkyl group; Y is independently selected from at least one of Zn, Co, Cu, Fe, Mg, La, Al, Ni, Ce, Ca, Mn, Sb, Ag, Pb, Zr, and Sn.

2. The Lewis acid-containing homogeneous catalyst according to claim 1, characterized in that R 1 , R 2 , R 3 Independently selected from at least one of -CH3, -CH2CH3, -(CH2)2CH3, and -(CH2)3CH3.

3. The Lewis acid-containing homogeneous catalyst according to claim 1, characterized in that: The anion is selected from Cl - Br - ,I - At least one of them.

4. The method for preparing a Lewis acid-containing homogeneous catalyst according to any one of claims 1 to 3, characterized in that: The steps include: S1, heating a reaction mixture containing a cation source, a halogenated acetic acid, and a solvent to react to obtain a precursor; The cation source is selected from compounds containing at least one structure of imidazoles, linear ammonium salts, and linear phosphonium salts; S2, subjecting the raw material mixture containing the precursor obtained in step S1 and the metal cation source to solid phase grinding reaction to obtain a Lewis acid imidazole ionic liquid.

5. The preparation method according to claim 4, characterized in that: In step S1, the cation source is selected from at least one of the compounds represented by the structures of formula Ia, IIa, and IIIa; Among them, R 1 , R 2 , R 3 At least one independently selected from a C1-C6 alkane group, a C2-C6 olefin group, an aromatic group, and a C2-C6 cycloalkyl group; Preferably, in step S1, the halogenated acetic acid is selected from at least one of chloroacetic acid, bromoacetic acid and iodoacetic acid; Preferably, in step S1, the solvent is selected from at least one of methanol, ethanol, acetonitrile, ethyl acetate, acetone, benzene, toluene and xylene.

6. The preparation method according to claim 4, characterized in that: In step S1, the ratio of the amount of halogenated acetic acid to the cation source and the solvent is 1 mol: 0.9-3 mol: 30-90 mL; Preferably, in step S1, the conditions for the heating reaction include: heating to 50-80° C. and reacting for 12-24 hours; Preferably, in step S1, the conditions for the heating reaction include: heating to 50-60°C, 60-70°C, and 70-80°C in sequence, and reacting for 12-24 hours respectively.

7. The preparation method according to claim 4, characterized in that: In step S2, the metal cation source is selected from at least one of zinc acetate, cobalt acetate, copper acetate, ferrous acetate, magnesium acetate, lanthanum acetate, aluminum acetate, nickel acetate, cerium acetate, calcium acetate, manganese acetate, antimony acetate, silver acetate, lead acetate, zirconium acetate, and tin acetate.

8. The preparation method according to claim 4, characterized in that: In step S2, the conditions for the solid phase grinding reaction include: the grinding time is 5 to 20 minutes.

9. Use of at least one of the Lewis acid-containing homogeneous catalysts according to any one of claims 1 to 3 or the Lewis acid-containing homogeneous catalysts prepared according to the preparation method according to any one of claims 4 to 8 in catalyzing the cycloaddition reaction of epoxides and CO2 to prepare propylene carbonate.

10. The use according to claim 9, characterized in that: The epoxide is selected from ethylene oxide, propylene oxide, 1,2-butylene oxide, epichlorohydrin, glycidol, styrene oxide, phenyl glycidyl ester and allyl glycidyl ester; Preferably, the reaction temperature window of the homogeneous catalyst is 80-160°C.

Citation Information

Patent Citations

  • Metal complex catalyzer and application thereof for synthesizing cyclic carbonate

    CN102671703A

  • Metal ionic liquid, preparation method thereof, and application of metal ionic liquid in catalyzing cycloaddition reaction of carbon dioxide to prepare cyclic carbonate

    CN110885314A

  • Ethylene carbonate hydrogenation heterogeneous catalyst as well as preparation method and application thereof

    CN110975939A